Mathematics Learning With Metacognitive Instructions In Malay Culture - Nur Rahmi Rizqi; Jihan Hidayah Putri; Israq Maharani; Nur Rahmi Rizqi (JURNAL MATHEMATIC PAEDAGOGIC, 2023)
The Purpose of conducting this research is to find out the relationship between mathematics learning and metacognition instruction based on Malay culture. In this study, using a descriptive research strategy, namely describing and explaining field variables based on existing literature (literature review). The results and discussion are that learning mathematics accompanied by metacognition instructions in Malay culture can be associated with reciprocating rhymes in Malay culture. This link is based on metacognition itself guiding in the right direction by asking questions that can lead, explore, and generalize. While reciprocating rhymes that provide a goal as a role model.  Based on metacognition that guides in directing questions from leading, exploring and generalizing combined with rhymes in order to get the desired learning objectives.So that learning mathematics accompanied by metacognition instructions can be associated with reciprocating rhymes in Malay culture.